Shipboard trials of magnesium-based exhaust gas cleaning system. (1st December 2016) - Zhu, Yimin; Tang, Xiaojia; Li, Tie; Ji, Yangyuan; Liu, Quan; Guo, Lin; Zhao, Jiao
Abstract: In this paper, the shipboard trials were conducted to investigate the efficacy of a magnesium-based exhaust gas cleaning system (Mg-EGCS) and the life cycle cost analysis method was utilized to evaluate the economic benefit of Mg-EGCS. The shipboard trials results indicated that the measured sulfur dioxide reduction was excellent, well within the IMO's most stringent limits at any test loads. The discharge water was in compliance with IMO's guidelines for exhaust gas scrubbers. Furthermore, the pressure drop was less than 400 Pa, which was far below a nominal scrubber pressure drop of 1500 Pa. The internal rate of return (IRR) value of Mg-EGCS implied that it had obvious economic advantage compared with the conventional closed loop, hybrid and dry system. Highlights: Magnesium-based EGCS was used for marine engine exhaust gas desulphurization. The measured sulfur reduction was well within the IMO's most stringent limits. Exhaust fan was unnecessary for the system because of the low pressure drop. High internal rate of return (IRR) value.